2015
DOI: 10.1161/atvbaha.114.304768
|View full text |Cite
|
Sign up to set email alerts
|

Etv2 and Fli1b Function Together as Key Regulators of Vasculogenesis and Angiogenesis

Abstract: Objective The E26 transformation-specific domain transcription factor Etv2/Etsrp/ER71 is a master regulator of vascular endothelial differentiation during vasculogenesis, although its later role in sprouting angiogenesis remains unknown. Here, we investigated in the zebrafish model a role for Etv2 and related E26 transformation-specific factors, Fli1a and Fli1b in developmental angiogenesis. Approach and Results Zebrafish fli1a and fli1b mutants were obtained using transposon-mediated gene trap approach. Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 50 publications
4
66
0
Order By: Relevance
“…There are multiple ETS family members, but of these ETS-1 and ERG are highly expressed in the vasculature and have been shown to be regulated by VEGF signaling [27, 28]. The FOXO family of transcription factors has been implicated in metabolism, proliferation and longevity in endothelial cells [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple ETS family members, but of these ETS-1 and ERG are highly expressed in the vasculature and have been shown to be regulated by VEGF signaling [27, 28]. The FOXO family of transcription factors has been implicated in metabolism, proliferation and longevity in endothelial cells [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Despite dramatic defects in early vasculogenesis, vascular development partially recovers even in etv2 null mutant zebrafish embryos at later stages, and only aberrant angiogenesis is observed during later stages. This later recovery is mediated by related ETS transcription factors such as Fli1b which functions redundantly with Etv2 during later stages of vasculogenesis and during angiogenesis [10]. Overexpression of Etv2 results in dramatic expansion of hemangioblast and vascular endothelial marker expression in either zebrafish or Xenopus embryos, demonstrating that a single transcription factor is sufficient to induce vascular endothelial fate in different cell types [18, 21].…”
Section: Ets Factors In Vascular Developmentmentioning
confidence: 99%
“…In contrast, a separate study demonstrated that Flk1:Cre; Etv2 conditional mouse knockout embryos displayed disorganized vasculature and reduced hematopoietic progenitors cells and died at 10.5 [11]. Conditional Etv2 knockdown in zebrafish embryos using photoactivatable caging strand hybridized to a morpholino also demonstrated lack of vascular phenotype when Etv2 function is inhibited at 18-somite or later stages after the initial vasculature has formed [10, 22, 36]. However, recent studies show that Etv2 functions redundantly with other ETS transcription factors during later angiogenesis stages [10], which may explain the absence of the phenotype in mouse Flk1:Cre conditional Etv2-knockout embryos.…”
Section: Ets Factors In Vascular Developmentmentioning
confidence: 99%
See 2 more Smart Citations